The impact of packaging element towards customer purchasing behavior for Agromas products / Amir Haziq Zaini - Zaini, Amir Haziq (Faculty of Business and Management, 2014)
The research of the impact of packaging towards Agromas product provided by Federal Agricultural Marketing Authority has conducted. The Agromas product cannot be exist without customer. As such, the customer must be the central focus of the organization. This research has been determined whether the element of packaging will give affect toward customer purchasing behavior for Agromas product. In this study, the researcher collects the information from the primary.